Austerity Politics and the Post-Politicisation of Conservation Governance in Canada - Megan Youdelis (Conservation & Society, 2018)
Several notable controversies around private sector interests in national parks throughout Canada have erupted within the last five years. These controversies are arising within the context of budget cuts to Parks Canada and related imperatives to increase visitor numbers and 'visitor experience' to recoup costs and strengthen public support for Canadian parks. While the majority of the literature on the neoliberalisation of conservation focuses on its socio-environmental implications, this research highlights some important political implications of the increasing role of private interests in conservation practice due to state level austerity politics. This article outlines the post-politics of public consultation in Jasper National Park through a study of two public contestations around private tourism development in the park. I argue that austerity politics create the conditions for a re-articulation of the politics of conservation governance as the interests of parks departments and private sector interests are brought into alignment. Austerity-related restructuring of conservation practice elevates the importance of public-private partnerships for sustaining the viability of the park system, contributing to the construction of a post-political 'there is no alternative' discourse where neoliberal ideology in conservation is elevated beyond critique. To facilitate development, managers employ various strategies to reduce democratic oversight of public provisioning, removing opportunities for political debate and dissensus and orchestrating the appearance of consensual decision-making.